2022
DOI: 10.3390/coatings12060798
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Corrosion of Copper and Its Alloy Coated with Hydrothermal Carbon

Abstract: Nonferrous materials such as copper and its alloys are sensitive to seawater corrosion. In this work, a hydrothermal carbonization coating was deposited on a C26000 brass and pure copper. The effectiveness of the coating on improving seawater corrosion performance was examined. First, hydrothermal carbonization of sugar (with 10 wt.% sucrose in water) at 200 °C and 1.35 MPa for 4 h was performed to generate the carbon-rich coating. The results of surface morphology, composition, hardness, thickness, and wettab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…To improve the corrosion resistance of copper-zinc alloys to seawater in the marine environment, hydrothermal synthesis of a carbonized coating was conducted in [5]. Although hydrothermal synthesis [6] has been reported for nanomaterial production, its new application for making surface coatings to protect materials from corrosion is introduced in this paper [5]. The hydrothermal carbonization coating was formed on both brass (a Cu-Zn alloy with the designation of C26000) and pure copper.…”
mentioning
confidence: 99%
“…To improve the corrosion resistance of copper-zinc alloys to seawater in the marine environment, hydrothermal synthesis of a carbonized coating was conducted in [5]. Although hydrothermal synthesis [6] has been reported for nanomaterial production, its new application for making surface coatings to protect materials from corrosion is introduced in this paper [5]. The hydrothermal carbonization coating was formed on both brass (a Cu-Zn alloy with the designation of C26000) and pure copper.…”
mentioning
confidence: 99%
“…It is confirmed that Pt as a dopant has a critical role in improving the conductive behavior and enhancing the corrosion resistance of nitride coatings for potential applications in off-shore structures. To increase the seawater corrosion resistance of a copper-zinc alloy in the marine environment, a hydrothermally carbonized coating was prepared [8]. The hydrothermal processing method [9] has been studied for nanomaterial production.…”
mentioning
confidence: 99%
“…The hydrothermal processing method [9] has been studied for nanomaterial production. However, its new application for making surface coatings to slow down material degradation is only introduced in this study [8]. The hydrothermally carbonized coatings were deposited on both pure copper and its alloy, C26000 brass.…”
mentioning
confidence: 99%